Low-fat, high-protein, and fiber drink as an alternative to daily snack - Susyani Susyani; Muzakar Muzakar; Nuryanto Nuryanto (AcTion: Aceh Nutrition Journal, 2023)
Obesity is one of the causing factors of various degenerative diseases. Walnuts, almonds, pumpkin seeds, chia seeds, oats, and soy milk are nutritional ingredients that can help prevent disease and have the potential to be developed as health drink products. This study aims to make a supplement drink and find the results of the organoleptic test and its nutritional content. This study is an experimental, non-factorial, Completely Randomized Design with four treatments and three repetitions. The study was conducted in the Laboratory of Nutrition Department of Health Polytechnic of Palembang from March to April 2022. Organoleptic test data were analyzed using Kruskal-Wallis Test. The results showed that the best acceptance is the F1 formula. Based on Kruskal Wallis Test, it shows that the amount of composition of each ingredient makes a significant difference to organoleptic quality parameters of color (p=0,046) and taste (p=0,046) between formula In 100 grams of powder contains 381,65 kcal of energy, energy from fat 13,41 kcal, protein 26,31%, fat 1,49%, carbohydrates 65,75%, dietary fiber 22,54%, water content 3,53 %, ash content 2,92%, vitamin B3 0,87 mg, vitamin E 2,28 mg, omega 3 117,9 mg, omega 6 705,6 mg, linolenic acid 0,12%, unsaturated fatty acids monounsaturated 0,49%, polyunsaturated fatty acids 0,82%, calcium 166,31 mg, Fe 4,28 mg, magnesium 286,64 mg, selenium 21,61 mcg, and chromium 12,61 mcg. In conclusion, Fortipro Blended is low in fat, high in protein, and high in fiber based on the nutrient analysis test results.